Predictors and Correlates of Perceived Cognitive Decline in Retired Professional Rugby League Players - Van Patten, Ryan; Iverson, Grant L.; Terry, Douglas P.; Levi, Christopher R.; Gardner, Andrew J. (Frontiers in Neurology, 2021)
Objective: Rugby league is an international full-contact sport, with frequent concussive injuries. Participation in other full-contact sports such as American football has been considered to be a risk factor for neuropsychiatric sequelae later-in-life, but little research has addressed the mental and cognitive health of retired professional rugby league players. We examined predictors and correlates of perceived (self-reported) cognitive decline in retired National Rugby League (NRL) players. Methods: Participants were 133 retired male elite level rugby league players in Australia. Participants completed clinical interviews, neuropsychological testing, and self-report measures. The Informant Questionnaire on Cognitive Decline in the Elderly, self-report (IQCODE-Self), measured perceived cognitive decline. Results: The median age of the sample was 55.0 (M = 53.1, SD = 13.9, range = 30–89) and the median years of education completed was 12.0 (M = 11.9, SD = 2.6, range = 7–18). The retired players reported a median of 15.0 total lifetime concussions (M = 28.0, SD = 36.6, range = 0–200). The mean IQCODE-Self score was 3.2 (SD = 0.5; Range = 1.3–5.0); 10/133 (7.5%) and 38/133 (28.6%) scored above conservative and liberal cutoffs for cognitive decline on the IQCODE-Self, respectively. Perceived cognitive decline was positively correlated with current depressive symptoms, negatively correlated with years of professional sport exposure and resilience, and unrelated to objective cognition and number of self-reported concussions. A multiple regression model with perceived cognitive decline regressed on age, concussion history, professional rugby league exposure, depression, resilience, objective cognitive functioning, daytime sleepiness, and pain severity showed depression as the only significant predictor. Conclusion: This is the first large study examining subjectively experienced cognitive decline in retired professional rugby league players. Similar to studies from the general population and specialty clinics, no relationship was found between objective cognitive test performance and perceived cognitive decline. Depressive symptoms emerged as the strongest predictor of perceived cognitive decline, suggesting that subjective reports of worsening cognition in retired elite rugby league players might reflect psychological distress rather than current cognitive impairment.